2015
DOI: 10.1016/j.janxdis.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity and the anticipation of predictable and unpredictable threat: Evidence from the startle response and event-related potentials

Abstract: There is growing evidence that heightened sensitivity to unpredictable threat is a core mechanism of dysfunction in anxiety disorders. However, it is unclear whether anxiety sensitivity is also associated with sensitivity to unpredictable threat. In the present study, 131 participants completed the Anxiety Sensitivity Index–3, which includes physical concerns (PC), social concerns (SC), and cognitive concerns (CC) subscales, and a predictable vs. unpredictable threat-of-shock task. Startle eyeblink and ERP res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 99 publications
5
32
1
2
Order By: Relevance
“…It has been posited that heightened reactivity to an uncertain threat may stem from several related abnormalities including increased threat attention, inflated estimates of threat harm, deficient safety learning, and maladaptive cognitive control (Grupe and Nitschke, 2013). It has also been suggested that personality traits such as anxiety sensitivity (AS), or the tendency to interpret anxiety-related sensations as fearful and distressing (Reiss et al, 1986), also contribute to reactivity to an uncertain threat (Lejuez et al, 2000; Melzig et al, 2008; Nelson et al, 2015), and that AS in particular may be an overlapping, yet distinct, factor related to problematic alcohol use (Carleton et al, 2007; DeMartini and Carey, 2011). To date, no study has attempted to disentangle the roles of these potential processes and how they contribute to reactivity to an uncertain threat and problematic drinking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been posited that heightened reactivity to an uncertain threat may stem from several related abnormalities including increased threat attention, inflated estimates of threat harm, deficient safety learning, and maladaptive cognitive control (Grupe and Nitschke, 2013). It has also been suggested that personality traits such as anxiety sensitivity (AS), or the tendency to interpret anxiety-related sensations as fearful and distressing (Reiss et al, 1986), also contribute to reactivity to an uncertain threat (Lejuez et al, 2000; Melzig et al, 2008; Nelson et al, 2015), and that AS in particular may be an overlapping, yet distinct, factor related to problematic alcohol use (Carleton et al, 2007; DeMartini and Carey, 2011). To date, no study has attempted to disentangle the roles of these potential processes and how they contribute to reactivity to an uncertain threat and problematic drinking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Especially high levels of anxiety sensitivity-a dimensional trait measure of the belief that physiological symptoms might signal severe bodily circumstances-seem to be related to specific bodily threat such as breathlessness (Alius, Pan e-Farr e, von Leupoldt, & Hamm, 2013;Melzig et al, 2008). Moreover, the modulation of neural responses during the anticipation of threat has been shown to correlate with increased trait levels of (anxious) cognitive, as well as physical, concerns (Nelson, Hodges, Hajcak, & Shankman, 2015).…”
mentioning
confidence: 99%
“…As shown in Figure 3(a), after being subjected to the T7 cycle, the C3H/HeJ mice showed a significant enhancement of the magnitude of the startle response, a phenomenon which is known to be associated with anxiety disorder [9]. These mice also showed reduced PPI as evidenced by the average startle responses after three of the four levels of prepulses tested (Figure 3(b)).…”
Section: Enhanced Startle Reflex and Deficits In Ppi In The C3h/hej Micementioning
confidence: 92%